The grammatical term of Ibn Zakur In his book The Preciousness - Yousif Ahmed, Loma; Al-Athari, Bushra Abdul-Razzaq (Al-Adab Journal, 2020)
This research is taking place as the title suggests in an attempt to study an important aspect of the grammatical lesson, which is "the grammatical term".Grammar terms, developed and known by the grammarians; Because its matter is no less important than the birth and elaboration of grammatical laws, so grammarians have paid little attention to status, specificity, and composition.I chose Ibn Zakour El-Fassi and (his book, The Address of Nafasah in Explaining Enthusiasm), without other grammarians, because its works are distinguished by a beautiful and gentle workmanship and ease of expression.Then this study reveals to us through the evidences the grammatical terminology that Ibn Zakur presented and used, and was it transferred to others? Or did he have his own terminology? Did he add new terms